MANAGEMENT STRATEGIES FOR PREGNANT WOMEN WITH GENITAL CONDYLOMATOSIS IN THE SECOND AND THIRD TRIMESTERS OF GESTATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article is devoted to one of the most frequent manifestations of papillomavirus infection - condylomas detected in the II and III semesters of pregnancy and the rational introduction of such patients. Purpose: To determine the optimal management strategy for pregnant women diagnosed with genital condylomatosis during the second and third trimesters and to summarize relevant domestic and international research findings. Materials and Methods: The study included 80 pregnant women aged 17 to 30 years with genital condylomatosis. All participants underwent HPV blood testing, cytological examination, colposcopy, and concurrent treatment of sexual partners. Conclusion: The combination therapy, which included Viferon, Acyclovir, Epigen spray, and cryodestruction – adjusted to the trimester of pregnancy – and laser coagulation, proved effective in accelerating the resolution of HPV-associated lesions. This approach significantly reduced recurrence rates and lowered the risk of carcinogenesis due to enhanced HPV elimination. The treatments demonstrated good tolerability and compatibility, making them suitable for broader clinical use in managing HPV during pregnancy.